Minimal‐access retroperitoneal pancreatic necrosectomy for infected necrotizing pancreatitis: a multicentre study of a step‐up approach. Issue 10 (25th May 2020) - Liu, Z.‐W.; Yang, S.‐Z.; Wang, P.‐F.; Feng, J.; He, L.; Du, J.‐D.; Xiao, Y.‐Y.; Jiao, H.‐B.; Zhou, F.‐H.; Song, Q.; Zhou, M.‐T.; Xin, X.‐L.; et al.
Abstract : Background: Various minimally invasive approaches have been described for infected necrotizing pancreatitis. This article describes a modified minimal‐access retroperitoneal pancreatic necrosectomy (MARPN) procedure assisted by gas insufflation. Methods: This retrospective, observational study documented patients who had undergone a step‐up MARPN between 1 January 2010 and 31 December 2016. A minimum follow‐up of 1 year was required for inclusion. The step‐up approach involved percutaneous catheter drainage followed by the modified MARPN and necrosectomy. If more than one access site was needed it was categorized as complex MARPN. Results: Of 212 patients with infected necrotizing pancreatitis, 164 (77·4 per cent) underwent a step‐up approach. The median number of percutaneous catheter drains and MARPN procedures was 3 (range 1–7) and 1 (1–6) respectively. Ninety patients (54·9 per cent) underwent complex MARPN. For residual necrosis after MARPN, three patients (1·8 per cent) underwent sinus tract gastroscopy, and 11 (6·7 per cent) had sinography combined with a tube change. However, operations in 13 patients (7·9 per cent) required conversion to open surgery. Postoperative complications developed in 103 patients (62·8 per cent). The mortality rate was 6·1 per cent (10 deaths). Conclusion: A step‐up approach using a modified MARPN for infected necrotizing pancreatitis is a reasonable option. Abstract : Minimally invasive approaches have been used increasingly in the management of infected necrotizing pancreatitis. This study presents a modified minimal‐access retroperitoneal pancreatic necrosectomy procedure assisted by carbon dioxide insufflation, instead of saline. A clear field of view without necrotic debris floating in saline makes the technique safe and efficient. High degree of success VIDEO Presented in part to the Joint Congress of the Sixth Biennial Congress of the Asian–Pacific Hepato‐Pancreato‐Biliary Association and the 29th Meeting of the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery, Yokohama, Japan, June 2017 Abstract : Antecedentes: Los procedimientos mínimamente invasivos se han convertido en los más frecuentes para el tratamiento de necrosis pancreáticas infectadas. El objetivo de este estudio fue presentar un procedimiento de necrosectomía pancreática retroperitoneal de acceso mínimo ( minimal‐access retroperitoneal pancreatic necrosectomy, MARPN) modificado y asistido mediante insuflación de gases, así como evaluar su seguridad y eficacia. Métodos: Se realizó un análisis retrospectivo y observacional de los datos de un hospital desde el 1 de enero de 2010 hasta el 31 de diciembre de 2016. Se incluyeron en el análisis todos los pacientes en los que realizó un abordaje por etapas, que consistía en el drenaje percutáneo mediante la colocación de un catéter seguido de un procedimiento MARPN modificado, en los que se dispusiese de un seguimiento postoperatorio mínimo de 1 año. El MARPN en el lado derecho y la necrosectomía realizada a través de más de un acceso se clasificaron como MARPN complejo. Se evaluaron los resultados radiológicos y quirúrgicos. Resultados: De 212 pacientes con necrosis pancreática infectada, en 164 (77, 4%) se realizó un abordaje por etapas. La mediana del número de drenajes percutáneos y procedimientos MARPN fue 3 (rango, 1‐7) y 1 (rango, 1‐6), respectivamente. En 90 pacientes (54, 9%) se realizó un MARPN complejo. Para la exéresis de necrosis residual después de un MARPN, en 3 pacientes (1, 8%) se realizó mediante gastroscopia y en 11 pacientes (6, 7%) con un recambio de drenaje bajo control radiológico. En 13 pacientes (7, 9%) fue necesaria la reconversión a cirugía abierta. Hubo complicaciones postoperatorias en 103 pacientes (62, 8%). La tasa de mortalidad fue del 6, 1% ( n = 10). Conclusión: El abordaje por etapas con un MARPN modificado es seguro y efectivo en el tratamiento de la necrosis pancreática infectada.